Corporate social responsibility in FC Barcelona as Carroll’s CSR pyramid in practice - Marek, Agnieszka (Annales. Etyka w Życiu Gospodarczym, 2019)
Corporate social responsibility (CSR) is a subject of great interest to both theoreticians and practitioners of management as well as to international organisations that promote this idea among existing enterprises. Despite many years of research on CSR, there is no single binding definition of this concept, therefore for the needs of this publication, the definition of Archie B. Carroll, and the resulting approach to CSR implementation in companies, has been adopted. The aim of the article is to analyse CSR activities undertaken by FC Barcelona in the framework of a system derived from Carroll’s CSR pyramid, therefore its activities have been divided into four groups corresponding to the dimension of financial, legal, ethical and philanthropic responsibilities. Due to the commercialisation of football, FC Barcelona is treated as a global enterprise, considering, however, the specificity of regulations governing the sports sector as well as goods and services offered by the club. The research has been based on an analysis of literature and available documents published by the club itself as well as by international organisations regulating football tournaments on national and international levels. The study has indicated that FC Barcelona is taking action in all the dimensions of social responsibility highlighted in Carroll’s pyramid and can be seen as a socially responsible organisation, at the same time meeting expectations of its stakeholders.